2017
DOI: 10.1146/annurev-genom-091416-035314
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in DNA Damage–Transcription Crosstalk and High-Resolution Mapping of DNA Breaks

Abstract: Until recently, DNA damage arising from physiological DNA metabolism was considered a detrimental by-product for cells. However, an increasing amount of evidence has shown that DNA damage could have a positive role in transcription activation. In particular, DNA damage has been detected in transcriptional elements following different stimuli. These physiological DNA breaks are thought to be instrumental for the correct expression of genomic loci through different mechanisms. In this regard, although a plethora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 149 publications
3
35
1
Order By: Relevance
“…These events are reminiscent of those at the centromeric locus in Schizosaccharomyces pombe , where small RNAs generated by Dicer bind to a nascent transcript that is also their precursor and together maintain the epigenetic and genetic stability of the locus 41 . The proposed model fits with the growing list of small ncRNAs interacting with and regulating long ncRNAs 42 and, more in general, with the emerging interplay between DSB and transcriptional control 43 .…”
Section: Discussionsupporting
confidence: 60%
“…These events are reminiscent of those at the centromeric locus in Schizosaccharomyces pombe , where small RNAs generated by Dicer bind to a nascent transcript that is also their precursor and together maintain the epigenetic and genetic stability of the locus 41 . The proposed model fits with the growing list of small ncRNAs interacting with and regulating long ncRNAs 42 and, more in general, with the emerging interplay between DSB and transcriptional control 43 .…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it is very likely these quercetin-like flavonoids have histone modifying functions as well. Besides histone acetylation, four compounds including sanguinarine, wortmannin, hypocrellin B, and radicicol are known to induce DNA damage, inhibit DNA repair or DNA topoisomerase II activity (Xu et al, 1998 ; Hashimoto et al, 2003 ; Barker et al, 2006 ; Matkar et al, 2008 ), which has been recently revealed to exert a positive role in initiation of gene transcription (Pommier et al, 2016 ; Vitelli et al, 2017 ). Additionally, radicicol, sclerotiorin, and sanguinarine are capable of inhibiting heat shock protein 90 (HSP90) (Davenport et al, 2014 ; Kabbaj et al, 2015 ; Khandelwal et al, 2016 ), which is known to interact with DNA topoisomerase II (Barker et al, 2006 ) and whose activity is regulated by reversible acetylation (Prodromou, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…If this spatiotemporal process is altered by misregulation of an RT‐related gene or a replication process step, e.g. replication licensing* , the propensity to DSB formation due to replication–transcription collision increases . In this regard, low‐density replication–initiation may lead to unfinished replication, owing to the long distance between replication forks, making breakage a probable event .…”
Section: Ddr–pdr: An Integrated Genome–proteome Maintenance Networkmentioning
confidence: 99%